Rancang Bangun Sistem Monitoring Aktivitas Pengguna Hotspot UNIDA Gontor Menggunakan Rsyslog dan Mikrotik API - Reyhan Nafis Ibrahim; Aziz Musthafa; Oddy Virgantara Putra (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
The current Covid-19 pandemic has made the need for the internet to increase among the public and academics. In addition to having a positive impact in increasing users, this can also have a negative impact that is at risk of violations in internet use. Therefore, it is necessary to build a monitoring system for more intense monitoring of student internet activities while using campus internet services. In analyzing and implementing the system, this study uses the Network Development Life Cycle (NDLC) method. To obtain data, the system is integrated with network sources using the Mikrotik Application Programming Interface (API) and Rsyslog. Network administrators can register hotspot user accounts, monitor hotspot network status, view and record student internet browsing history, and filter results for sites that are worth accessing and not by matching available data using the Mikrotik API and Rsyslog. System testing is carried out using API testing and distributing questionnaires to 10 respondents from the Information and Communication Technology Service Center staff who get an average score of 91 with excellent predicate. It is hoped that in the future this monitoring system can reduce the number of student violations during internet use and can be applied to all internet networks distributed at Darussalam Gontor University